2013
DOI: 10.1371/journal.pone.0055219
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Virulence Markers among Vibrio vulnificus Isolates of Clinical and Environmental Origin and Regional Characteristics in Japan

Abstract: Background Vibrio vulnificus is an opportunistic human pathogen that is widely distributed in estuarine environments and is capable of causing necrotizing fasciitis and sepsis. In Japan, based on epidemiological research, the incidences of V. vulnificus were concentrated in Kyusyu, mainly in coastal areas of the Ariake Sea. To examine the virulence potential, various genotyping methods have recently been developed. This study aimed to investigate the distribution of virulence markers among V. vulnificus isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 36 publications
2
12
0
Order By: Relevance
“…A marginal association ( p = 0.097) was observed for the 16S rRNA and pilF genotypes, with degrees of association < 50%. Our results are consistent with those of a recent study of VV strains isolated in Japan [ 38 ]. In this study, P genotypes for the 16S rRNA gene, CPS, and vcg dominated both in clinical strains and in environmental strains.…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…A marginal association ( p = 0.097) was observed for the 16S rRNA and pilF genotypes, with degrees of association < 50%. Our results are consistent with those of a recent study of VV strains isolated in Japan [ 38 ]. In this study, P genotypes for the 16S rRNA gene, CPS, and vcg dominated both in clinical strains and in environmental strains.…”
Section: Resultssupporting
confidence: 94%
“…To evaluate and predict the virulence of different V . vulnificus strains, several genotyping methods have been developed [ 30 38 ]. Although genotyping studies are not a substitute for animal models for evaluating the virulence of V .…”
Section: Introductionmentioning
confidence: 99%
“…Several MLST analyses conducted on V. vulnificus demonstrated that the majority of strains of MLST cluster II are of clinical origin [ 8 , 9 , 10 , 11 , 16 , 37 ]. This cluster is also highly correlated with the clinical associated alleles of the vcg and 16S rRNA genes ( vcg -type C, 16S rRNA-type B) that are often used to predict strain virulence [ 12 , 13 , 39 ]. In addition, the majority of cluster II strains are positive for the nanA gene, region XII, and mannitol fermentation which are traits associated with clinical origin [ 10 , 11 , 16 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, we used gene targets commonly found among clinical isolates, including the thermostable direct and related hemolysins ( trh and tdh respectively) (Bej et al ., ) of V. parahaemolyticus , the siderophore‐related viu B (Panicker et al ., ) of V. vulnificus , and the wbe O and rfb specific to V. cholerae O1 and O139 serotypes (Hoshino et al ., ; Rivera et al ., ), as well as ctx A (encoding the A subunit of cholera toxin) (Fields et al ., ), tox R (a global regulatory gene) and tcp A (encoding the toxin‐coregulated pilus) (Rivera et al ., ) of V. cholerae . Although previous studies have shown the siderophore‐encoding viu B of V. vulnificus to be preferentially distributed among clinical isolates (Panicker et al ., ; Han et al ., ), additional studies suggest this gene may be widely distributed among environmental strains (Bogard and Oliver, ; Yokochi et al ., ).…”
Section: Introductionmentioning
confidence: 97%